THE "VOICE" IN COMPOSITION: REVIEWING THE ESSENCE OF WRITING CULTURALLY IN ENGLISH FOR MINANGKABAU-INDONESIAN EFL STUDENTS - Syayid Sandi Sukandi (Proceedings of ISELT FBS Universitas Negeri Padang, 2015)
Students who are studying English in the environment of EFL context, like those in lndonesia, usually feel afraid to write argumentatively and persuasively in the form of essay when they write: about topics that are of sensitive issues to them. If they are brave to do so, they basically frame their thoughts from the angle of being an Indonesian who is filled with prescriptive cultural backgrounds. To be able to argue within their own ideas is what they are generally good the most, even though syntactically and grammatically their writing has certain level of linguistic deficiency. At this point, teaching these types of students to write within their own "voice" is what they need in order to reach the point of being able to express their thoughts. Other aspects of standard academic essay writing, especially in terms of grammar and vocabulary. should follow general concepts along the lines with their ability to express their thoughts. In this writing, holistic views toward the process of learning writing in an EFL context are briefly discussed. From the consulted literature on EFL studies, it can be concluded that considering grammar and vocabulary too much before the act of writing handicaps students' process in composing solid essay. The solution to this type of EFL pedagogical matter is to help them in letting go their 'voice" in writing so that the essence of their writing becomes alive and communicative to their targeted readers; in other words, their writings speak beyond grammar.